Komunikasi Kelompok dan Keselamatan Kerja (Studi Kasus tentang Komunikasi Kelompok dalam Meningkatkan Keselamatan Kerja bagi Penambang Pasir di Kabupaten Banyumas) - dwi pangastuti (Jurusan Ilmu Komunkasi FISIP Universitas Jenderal Soedirman, 2011)
River Sand miners are one of informal occupations which are still for from both concern anddevelopment particularly in terms of its health as well as health safety. This high – risk job to boththemselves and environment is always conducted through teamwork.A primary as well as secondary small group is a mean of people to manifest their hope andshare of information in most aspects of life. Taking is respondents in Sidabowa, Patikraja,Banyumas Regency as the sample, the researcher observed how the role of Group CommunicationPlays among the sand river miners toward their health safety.Through an analytical descriptive approach, it is obtained that Group Communication Playsa significant role in improving cooperation among members. By Group Communication, a widerange of information is gained as an effort to achieve the health safety.